Remotely controlled and drive system design on mini omdirectional mobile manipulator arm - Muhammad Afiq, Ruslli (2022)
Many scholars have recently focused their efforts on research concerning wheeled omnidirectional running devices. In the military, storage and transportation, social services, and other industries, mecanum omnidirectional vehicles have found broad use. In terms of mobility in narrow spaces and congested environments, omnidirectional robotic vehicles have various benefits over traditional vehicles. In congested environments with static obstructions, dynamic obstacles, or confined spaces, they can easily complete some tasks. The first challenge in omnidirectional mobile manipulator arm is controlling the arm and vehicle simultaneously using a single controller since the existing system the vehicle and the arm are controlled separately. On the other hand, the electronic and power management also the challenge in built this system. This requires modifying the present code for arm, mecanum, and grasper, as well as remote configuration. Solutions for the electronic system and power management is modified current drive code for each driver, power management, and design of the main controller circuit. The expected result for this project is to establishing remotely control for both mecanum and its manipulator arm. This result can be achieved by first combine both mecanum manipulator arm. Next, all the motor are connected to Arduino board containing programming codes that can remotely control both mecanum and its manipulator arm. Then, execute the programming codes. This will result in design and establishing remotely control for both mecanum and its manipulator arm.